1998
DOI: 10.1152/ajpcell.1998.274.1.c120
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Ca2+-gated cardiac muscle Ca2+-release channel (ryanodine receptor) by mono- and divalent ions

Abstract: The effects of mono- and divalent ions on Ca2+-gated cardiac muscle Ca2+-release channel (ryanodine receptor) activity were examined in [3H]ryanodine-binding measurements. Ca2+ bound with the highest apparent affinity to Ca2+activation sites in choline chloride medium, followed by KCl, CsCl, NaCl, and LiCl media. The apparent Ca2+ binding affinities of Ca2+ inactivation sites were lower in choline chloride and CsCl media than in LiCl, NaCl, and KCl media. Sr2+ activated the ryanodine receptor with a lower effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
3

Year Published

2000
2000
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(55 citation statements)
references
References 24 publications
8
44
3
Order By: Relevance
“…This change seems to be different from the results obtained by single-channel recording [21,22] . The exact reason for this discrepancy is unclear.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This change seems to be different from the results obtained by single-channel recording [21,22] . The exact reason for this discrepancy is unclear.…”
Section: Discussioncontrasting
confidence: 99%
“…Role of ionic strength Previous studies have indicated that the activity of RyRs and the interaction between RyRs are modulated by ionic strength. For instance, with singlechannel recording an increase of RyR activity has been shown with increasing KCl concentration [21,22] . By photon Each curve was obtained from ≥634 events (Ca 2+ sparks).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a controversy about the existence of CaI on RyR2s [4]. Recently, it is shown that high [Ca 2+ ] f could evidently decrease the binding to the SR of canine heart, indicating the presence of CaI on RyR2s [14]. This proposal is supported by the present study (Fig.…”
Section: +supporting
confidence: 90%
“…We showed clearly the effectiveness of the I-site, although RyR2 shows a lower affinity than RyR1 and RyR3 (Table 1). One explanation for this discrepancy is the difference in experimental conditions: a high salt-medium, 1 M KCl, was used instead of 0.17 M KCl, and/or purified RyR2 was used for the experiments (8,14,15,18,34,37). Another explanation is the limited range of Ca 2ϩ concentrations of up to pCa 4 (14, 15).…”
Section: Discussionmentioning
confidence: 99%